2022
DOI: 10.1021/acs.est.2c06168
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Wastewater Treatment Processes Can Be a Double-Edged Sword for Water Quality Improvement in View of Mitigating Antimicrobial Resistance and Pathogenicity

Abstract: Despite the high removal efficiency for chemical pollutants by tertiary wastewater treatment processes (TWTPs), there is no definite conclusion in terms of microbial risk mitigation yet. This study utilized metagenomic approaches to reveal the alterations of antibiotic resistance genes (ARGs), virulence factor genes (VFGs), their co-occurrence, and potential hosts during multiple TWTPs. Results showed that the TWTPs reduced chemical pollutants in wastewater, but the denitrifying biofilter (DB) significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Although ARG hosts during biological wastewater treatment vary in studies due to different operational parameters and antibiotics, heterotrophic denitrifiers reportedly exhibit strong associations with ARGs and serve as potential hosts. 34,41 However, it was also reported that the anammox bacterium Candidatus Brocadia is a host of SDZ and chlortetracycline resistance genes. 31 Herein, anammox bacteria were negatively correlated with most ARGs, which was contrary to the above finding.…”
Section: Microbial Response Of the Anammox Consortiamentioning
confidence: 99%
“…Although ARG hosts during biological wastewater treatment vary in studies due to different operational parameters and antibiotics, heterotrophic denitrifiers reportedly exhibit strong associations with ARGs and serve as potential hosts. 34,41 However, it was also reported that the anammox bacterium Candidatus Brocadia is a host of SDZ and chlortetracycline resistance genes. 31 Herein, anammox bacteria were negatively correlated with most ARGs, which was contrary to the above finding.…”
Section: Microbial Response Of the Anammox Consortiamentioning
confidence: 99%
“…Wastewater reuse, especially for agricultural irrigation in regions facing water scarcity such as the Middle East, North Africa, the Indian subcontinent, and the arid regions of northern China, holds significant importance . Efforts have been made to upgrade wastewater treatment plants to tertiary treatment levels in order to improve the water quality for agricultural irrigation . Among the techniques used in tertiary treatment to remove organic micropollutants from secondary wastewater, ozone stands out and is being widely adopted. However, several studies have indicated that even after ozone oxidation, pathogenic bacteria, such as Gram-negative bacteria, can remain in the wastewater and regrow during storage, leading to quantities equal to or even exceeding those found in untreated secondary wastewater. Recent research has attempted to address this issue by introducing natural competition as a method .…”
Section: Introductionmentioning
confidence: 99%
“…1 Efforts have been made to upgrade wastewater treatment plants to tertiary treatment levels in order to improve the water quality for agricultural irrigation. 2 Among the techniques used in tertiary treatment to remove organic micropollutants from secondary wastewater, ozone stands out and is being widely adopted. 3−5 However, several studies have indicated that even after ozone oxidation, pathogenic bacteria, such as Gram-negative bacteria, can remain in the wastewater and regrow during storage, leading to quantities equal to or even exceeding those found in untreated secondary wastewater.…”
Section: Introductionmentioning
confidence: 99%